1984
DOI: 10.1002/ajmg.1320170315
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic inversion duplication of chromosome 15 without phenotypic effect: Occurrence in a father and daughter

Abstract: A mosaic marker chromosome was observed in 2 generations. Multiple staining techniques identified it as an inverted duplication of chromosome 15 (inv dup 15) derived from the paternal grandmother. Although this inv dup 15 included a central R band, there was no noticeable phenotypic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…The inv dup(15) chromosomes in these individuals were known to be negative for the PWS/AS region by prior fluoresence in situ hybridization (FISH) analysis and uniparental disomy was excluded by previous microsatellite studies. Some of these individuals (the eight JC cases and case DL3, GM04347) have been described in part elsewhere (Knight et al 1984;Crolla et al 1995).…”
Section: Subjectsmentioning
confidence: 98%
“…The inv dup(15) chromosomes in these individuals were known to be negative for the PWS/AS region by prior fluoresence in situ hybridization (FISH) analysis and uniparental disomy was excluded by previous microsatellite studies. Some of these individuals (the eight JC cases and case DL3, GM04347) have been described in part elsewhere (Knight et al 1984;Crolla et al 1995).…”
Section: Subjectsmentioning
confidence: 98%
“…Most such individuals are ascertained through mental and/or developmental retardation (Schreck et al 1977;Wisniewski et al 1979;Maraschio et al 1981); however, reported phenotypes range from normal (Stetten et al 1981;Knight et al 1984) to Prader-Willi (Fujita et al 1980;Wisniewski et al 1980;Ledbetter et al 1982;Robinson et al 1993;Cheng et al 1994;Blennow et al 1995) or Angelman syndrome (Robinson et al 1993;Spinner et al 1995;Buchholz et al 1996) to the inv dup(15) syndrome (Wisniewski et al 1980;Zannotti et al 1980;Plattner et al 1991;Battaglia et al 1997). The inv dup(15) syndrome includes characteristics such as mild, moderate or severe mental and developmental retardation, seizures, autism or autistic traits, abnormal dermatoglyphics and strabismus (Zannotti et al 1980;Plattner et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Reports on individuals with milder phenotypes have been rare. Knight et al [1984] described a 10-year-old girl and her father, both of normal intelligence and with mosaicism for an inv dup(15)(q12) by G banding, but later, FISH studies were performed on the girl, then a 22-year-old woman, revealing a small inv dup(15) without the PWACR [Huang et al, 1997]. Chifari et al [2002] described a 25-year-old woman and an unrelated 27-year-old man, both with mild mental retardation becoming apparent at school age and non-mosaic large inv dup(15).…”
mentioning
confidence: 97%